The Intervention of Using Reciprocal Teaching Technique and Learning Styles on Students’ Reading Comprehension - Siti Habibah Egiyantinah; Alek Alek; Fahriany Fahriany; Ismail Suardi Wekke (AT-TA'LIM, 2018)
Reading is one of language skills that should be acquired by the students who learn English course in junior high school level. In learning a foreign language, students face many problems, especially in comprehending reading text. In reading process, the students have to understand the meaning of the text through their learning styles and combining their background knowledge, experiences, and situation with the information which is stated on the text. This article was to investigate the empirical evidence on the effect of Reciprocal Teaching Technique (RTT) Technique and learning styles on Students’ Reading Comprehension. The research was quantitative method and applied quasi-experimental design.  Sample of the research were chosen though simple random sampling technique. Data collecting technique of this research were pre-test and post-test. The data were analyzed by two-ways ANOVA. The findings of the recent study are: (1) there was an effect between teaching method and students’ learning styles on students’ reading comprehension, and (2) there were differences effect of students’ reading comprehension between students who own visual learning style in RTT group and those who own auditory learning style in class. It can be summed up that teaching through applying RRT technique which being supported by learning styles (visual and auditory) are to develop the students’ reading comprehension.